William E. Connolly's Politics of Complexity: A Critique. Issue 1 (9th January 2017) - Fear, Christopher
Abstract: In recent years, William E. Connolly has argued that the phenomenon of complexity in the physical sciences carries radical implications for political theory: namely, that political theorists should now be revising their concepts of agency, responsibility, and freedom. This very recent project of Connolly's has not (yet) attracted much opposition. Here I offer a critique of Connolly's argument which focuses on three key areas: (1) how he interprets and deploys "evidence" from physical science; (2) his theory of " creative freedom"; and (3) the impact that his recent philosophy has on the idea of the intellect. I argue that Connolly's scientific evidence is not what he claims it is; that the theory of "creative freedom" he offers fails; and that his critique of the intellect fails in theory, and would be highly damaging in practice.